Analysis of Income of Motorboat Workers with a 5 GT Capacity on the East and West Coast, Sumatra Utara - Lubis, Satia Negara; Jufri, Muhammad; Ulfa, Nadya (Talenta Publisher, 2021)
Sumatra Utara has a coastline of about 1.300 km, consisting of an east coast of 545 km, a west coast of 375 km and Nias Islands is about of 380 km which has a very large diversity of marine and fishery resources. This potential fishery potential can provide maximum benefits in a sustainable manner for the people of Sumatera Utara. However, there are many issues in the management of capture fisheries in Sumatra Utara sea, both overfishing and underfishing. This study aims to analyze the differences in the amount of operating costs, revenues and income of labor fishermen on the east and west coasts of Sumatra Utara. Using the method of revenue analysis, income analysis and paired sample t test. The results showed that the operating costs, revenues and income of labor fishermen on the east and west coasts of Sumatra Utara were 0.00 < 0.05 it means that there was a significant difference between operating costs, revenues, and income of East Coast labor fishermen and operating costs, revenues and income labor fishermen on the west coast of Sumatra Utara.